Anti-inflammatory effects of a novel non-antibiotic macrolide, EM900, on mucus secretion of airway epithelium. Issue 4 (August 2015) - Tojima, Ichiro; Shimizu, Shino; Ogawa, Takao; Kouzaki, Hideaki; Omura, Satoshi; Sunazuka, Toshiaki; Shimizu, Takeshi
Abstract: Objective: Low-dose, long-term use of 14-membered macrolides is effective for treatment of patients with chronic airway inflammation such as diffuse panbronchiolitis or chronic rhinosinusitis. However, long-term use of macrolides can promote the growth of drug-resistant bacteria, and the development of anti-inflammatory macrolides that lack antibiotic effects is desirable. Previously, we developed EM900, a novel 12-membered erythromycin A derivative, which has potent anti-inflammatory and immunomodulatory activities and lacks any antibacterial activity. We examined the anti-inflammatory effects of EM900 on mucus secretion from airway epithelial cells. Methods: To examine the in vivo effects of EM900 on airway inflammation, we induced hypertrophic and metaplastic changes of goblet cells in rat nasal epithelium via intranasal instillation of lipopolysaccharides. In vitro effects of EM900 on airway epithelial cells were examined using cultured human airway epithelial (NCI-H292) cells. Mucus secretion was evaluated via enzyme-linked immunosorbent assays with an anti-MUC5AC monoclonal antibody. Results: Oral administration of EM900 or clarithromycin (CAM) significantly inhibited LPS-induced mucus production from rat nasal epithelium. EM900, CAM, or erythromycin significantly inhibited MUC5AC secretion induced by tumor necrosis factor-α from NCI-H292 cells. MUC5AC mRNA expression was also significantly lower in EM900-treated cells. Conclusion: These results indicated that a novel non-antibiotic macrolide, EM900 exerted direct inhibitory effects on mucus secretion from airway epithelial cells, and that it may have the potential to become a new anti-inflammatory drug for the treatment of chronic rhinosinusitis.